Evaluating Power and Status in Turn-taking Mechanism in Insight with Desi Anwar Talk Show - Ema Sri Rahayu; Hendi Pratama; Puji Astuti (English Education Journal, 2023)
In a talk show, conversations naturally operate by taking turns. Sometimes the participants ignore the rules and focus more on gaining significant attention from the audience than making successful conversations. The participants involved in the conversation have the power to organize the distribution of conversational turns. This research applied qualitative research, which concerns evaluating the power and status of turn-taking mechanism used by the participants in talk show. The data used all utterances produced by participants from two episodes in Insight with Desi Anwar talk show. The utterances were transcribed using Jefferson's transcript notation. In addition, the data were analyzed by using the theories, such as Stenstrom, Sacks et al., and Brown and Levinson. The study reveals three findings related to the research questions. First, the results showed that taking the turn strategy was the most often used by the participants of the two episodes in talk show, followed by holding the turn strategy and yielding the turn strategy. Second, the phenomenon of turn-taking mechanism is influenced by power and status, where status affects participants in dominating turn-taking. Third, the quality of the conversation can be seen from the fluency of conversation itself in applying the rules of turn-taking mechanism. The participants use two rules, selecting the next speaker and self-selection. Pedagogically, this study can be used to make the teachers and students consider the significance of having an understanding of turn-taking mechanism, knowing the rules and how to maintain turn-taking, and the meaning of words in the spoken interaction.